THE INTEGRAL EDUCACION IN SCIENTIFIC PRODUCTION OF THESIS AND DISSERTATIONS IN EDUCATION (2010-2015) - Hayashi, Marcelo Innocentini [UNESP]; Miceli Kerbauy, Maria Teresa [UNESP] (Univ Estadual Paulista-unesp, Fac Ciencias Letras Assis, 2016)
The article provides a historical overview of integral education and public policies that have adopted this perspective and analyzes the scientific literature on this theme developed in brazilian's graduate programs in the period between 2010 and 2015 and indexed on these and dissertations databases. The results showed that the concept of holistic education has its origins in ancient Greece and comes to the present day. In Brazil, the integral education is effective as a public education policy from the 1990s, although there were previous experiences since the 1960s. The mapping of the scientific production presents a profile of academic research on the integral education expresses in the analyzed dissertations and theses, and the results showed the impact of public policies on comprehensive education in academic research. Most of the work on case studies on municipal or state public policies of integral education in predominating analyzes the experiences conducted in Minas Gerais, Sao Paulo, Goias and Rio Grande do Sul.
Keywords: Integral education; Public educacion policies; Scientific production